How policy discourses and contextual realities influence environmental teaching and learning processes in early childhood development: a case study of the Raglan Road child care centre - Vallabh, Priya (Rhodes University, Faculty of Education, Department of Education, 2005)
This case study considers the relationship between context, school policy and environmental teaching and learning processes at a community-based early childhood development centre in South Africa. The study recognises that educational practices in the early childhood development field are shaped by historical, cultural, economic and political realities at both local and national levels. It is from the understanding that each school is a unique composition of these shaping factors that the research was designed to consider the community-based school participating in this study. By compiling a contextual profile, this study attempts to consider dominant contextual factors affecting the school. Through the critical discourse analysis of a school policy document, this study considers local level policy, and through the literature chapter, national policy. Teacher interviews provide insight into teacher understanding of school policy in response to contextual issues, as well as providing insight into how teachers perceive their translation of policy into teaching practice. Observations of lessons in the centre provided an. opportunity to see how context and policy translated into and influenced environmental teaching and learning processes. This study looks at how environmental education is addressed in the Raglan Road Child Care Centre, and provides insight into how environmental education within the context of the school and in relation to school policy may be strengthened. It comments on the tensions and ambivalences arising from the relationships between context, policy and environmental teaching and learning processes and makes recommendations to address these ambivalences in ways that are contextually relevant. The main recommendations were designed to be practically useful for the school involved in the study and are focused around engaging the ambivalences emerging from this study to open up 'spaces' for deliberating environmental teaching and learning processes and other tensions arising out of the study at an ECD level. Recommendations included: 1) engaging with the strong development focus in school policy and the educational focus in national policy and teacher discourse; 2) deliberating the ways in which school policy and national policy respond to risk; 3) engaging with the ambivalence in the school-parent relationship; 4) the re-alignment of the explicit curriculum and broadening the contextually-based view of whole child development; and 5) engaging the ambivalence in approaches to education at the centre.
Keywords: Early childhood education -- South Africa; Health education -- South Africa; Environmental education -- Study and teaching -- South Africa; Day care centers -- South Africa; Child development